Stem Cell Therapy for Perianal Crohn’s Disease - O V Knyazev; N A Fadeeva; A V Kagramanova; N I Belyakov; N V Orlova; A A Lishchinskaya; A G Konoplyannikov; A I Parfenov (Терапевтический архив, 2018)
Aim. To compare the effectiveness of the effect of combination therapy (local and systemic administration) with bone marrow mesenchymal stromal cells (MSC), anticlitokine therapy with infliximab (IFX), and antibiotic (AB)/immunosuppressive (IS) therapy on the frequency of healing of simple perianal fistulas in Crohn's disease. Materials and methods. In our study, the 1-st group of patients aged 19 to 58 years (Me-29) (n = 12) received MSCs culture systemically according to the scheme and locally. The 2-nd group of patients with CD (n = 10) from 20 to 68 years old (Me-36) received anticytokine therapy with infliximab (IFX) according to the scheme. The 3-d group of patients with CD (n=14) from 20 to 62 years old (Me-28) received antibiotics (AB) and immunosuppressors (IS). Efficacy was assessed by the index of perianal activity of Crohn's disease (PCDAI) and the frequency of relapses. Results. After 12 weeks among patients of the 1-st group, healing of simple fistulas was noted in 8/12 patients (66.6%), in the 2-nd group in 6/10 (60.0%) In the 3-d group, in 1/14 patients (7.14%). After 6 months in the 1-st group of patients, healing of simple fistulas was preserved in 8/12 (66.6%), in the 2-nd group - in 6/10 (60.0%). In the 3-d group - in 1/14 patients (7.14%). After 12 months in the 1-st group, healing of simple fistulas was preserved in 7/12 (58.3%), in the second group - in 6/10 (60.0%). In the 3-d group - in 2/14 patients (14.3%). After 24 months, among the patients of the 1-st group, fistula closure was maintained in 5/12 patients (41.6%), in the 2-nd group - in 4/10 (40.0%). In the 3-d group - in 0/14 patients (0.0%). Conclusion. Combined cellular and anticytokine therapy of CD with perianal lesions significantly contributes to the more frequent and prolonged closure of simple fistulas, as compared to antibiotics/immunosuppressors, and to a decrease in the frequency of recurrence of the disease.